KEPUASAN MASYARAKAT ATAS KINERJA PELAYANAN PUBLIK (Studi pada Kantor Camat Peusangan Selatan Kabupaten Bireuen) - Rusli, Rusli; Kamaruddin, Kamaruddin; Abqa, Rizkan (Ekonomika Journal, 2024)
Public services are a series of activities in order to fulfill service needs in accordance with statutory regulations for every citizen, which are usually carried out by the government, including services at sub-district offices. In order for public satisfaction in services to be achieved, the performance factors of public service actors and trust need to be maintained and improved. This study relates to service satisfaction felt by the community in Peusangan sub-district, Bireuen Regency. Using the associative descriptive method relying on a sample of 96 respondents, representing the community in 25 villages, who carried out population administration at the sub-district office, the results were found; (1) public satisfaction is influenced by the performance of service employees, amounting to 36.28%, while the public service factor is 49.57% and public trust is 58.91%. (2) There is a significant causal relationship between performance, public service and public trust at a moderate level. And (3) If the contribution of the three factors, namely performance, service and public trust, to community satisfaction is very significant, it reaches 77.4%.